Dukungan Teman Sebaya berhubungan dengan Perilaku Pemeriksaan Payudara Sendiri sebagai Deteksi Dini Fibroadenoma Mammae pada Mahasiswi - Putri Ana, Ayu; Lutfiyati, Afi (HEALTHY BEHAVIOR JOURNAL, 2023)
Background: Fibroadenoma mammae (FAM) usually occurs in women aged <30 years. Women with FAM have an 8.95 times higher risk of developing breast cancer. Early detection measures could be done with breast self-examination (BSE). One of the factors that affect BSE is peer support. This study aimed to determine the association between peer support and BSE behavior as an early detection of mammary fibroadenoma in female students. Method: Type of research is quantitative study with a cross sectional approach. The population in this study were nursing students, amnouting to 218 female students. Samples were taken based on inclusion and exclusion criteria, selecting samples used a stratified random sampling technique with a sample size of 76 respondents. This research instrument used a questionnaire. Respondents had peer support the majority in the good category of 37 respondents (48.7%), most of BSE behavior were the sufficient category of 49 respondents (64.5%). Result: The result of several analyzes showed that there were a significant association between peer support and BSE behavior p-value of 0.001 (p<0.05), with a low association value of 0.392. There were an association between peer support and BSE behavior as an early detection of mammary fibroadenoma in female students. Conclusion: The advice given should be for female students to increase peer support in advocating and reminding them to do BSE.